2004
DOI: 10.1074/jbc.m407889200
|View full text |Cite
|
Sign up to set email alerts
|

Factor XI Interacts with the Leucine-rich Repeats of Glycoprotein Ibα on the Activated Platelet

Abstract: Factor XI (FXI) binds specifically and reversibly to high affinity sites on the surface of stimulated platelets (K d app of ϳ10 nM; B max of ϳ1,500 sites/platelet) utilizing residues exposed on the Apple 3 domain in the presence of high molecular weight kininogen and Zn 2؉ or prothrombin and Ca I-FXI to activated platelets. All leucine-rich repeat (LRR) peptides derived from glycoprotein Ib␣ were able to inhibit FXI binding to activated platelets in the following order of decreasing potency: LRR7, LRR1, LRR4, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
61
0
2

Year Published

2006
2006
2017
2017

Publication Types

Select...
7
2

Relationship

2
7

Authors

Journals

citations
Cited by 74 publications
(65 citation statements)
references
References 44 publications
2
61
0
2
Order By: Relevance
“…Furthermore, GPIb-V-IX binds with high affinity to thrombin, which can support thrombin-induced activation of the receptors PAR1 and PAR4, although the physiological importance of the GPIb pathway is debated (68). In addition, GPIb␣ has been reported to bind the coagulation factors FXI, FXII, and high-molecular-weight kininogen (7) and may also function as a coreceptor for FVIIa (314) and FXI(a) (17). On the other hand, recent findings suggest that FXI binds to platelets via the receptor LRP8 (ApoeER2) (317).…”
Section: A Platelet Leucine-rich Repeat and Immunoglobulin Family Rementioning
confidence: 99%
“…Furthermore, GPIb-V-IX binds with high affinity to thrombin, which can support thrombin-induced activation of the receptors PAR1 and PAR4, although the physiological importance of the GPIb pathway is debated (68). In addition, GPIb␣ has been reported to bind the coagulation factors FXI, FXII, and high-molecular-weight kininogen (7) and may also function as a coreceptor for FVIIa (314) and FXI(a) (17). On the other hand, recent findings suggest that FXI binds to platelets via the receptor LRP8 (ApoeER2) (317).…”
Section: A Platelet Leucine-rich Repeat and Immunoglobulin Family Rementioning
confidence: 99%
“…[2][3][4] Each subunit has 607 amino acids, with four 90-amino acid apple domains (A1-A4) that, in the FXI monomer, assemble into a saucer-shaped disc, with the protease domain resting on top in an arrangement that we have described as a cup and saucer. 5 Biochemical data have mapped protein interactions to the apple domains for diverse ligands, including substrate FIX, 6 thrombin, 7 platelet glycoprotein Ib, 8 and high-molecular-weight kininogen (HK), 9 but to date, no complex crystal structures have been determined to define the molecular basis of these interactions. 10 FXI circulates in complex with cofactor HK.…”
Section: Introductionmentioning
confidence: 99%
“…However recent observations cast considerable doubt on the conclusion that activated platelets can promote the feedback activation of FXI by thrombin (35)(36)(37). Therefore, in a revised model of the interactions of FXI and FXIa with the activated platelet surface (Figure 7), dimeric FXI in complex with either HK or prothrombin is shown to expose a site within the A3 domain that binds to glycoprotein Ibα on the activated platelet surface (12)(13)(14)(15)19). Since this interaction has been demonstrated to be reversible (13), and since it has not been rigorously demonstrated whether it is the plateletbound or soluble form of FXI that is converted to FXIa, the activation of FXI by FXIIa, FXIa or thrombin is shown in Figure 7 to occur in solution.…”
Section: Discussionmentioning
confidence: 99%
“…In contrast, neither resting nor thrombin-activated human umbilical vein endothelial cells have any capacity to bind FXI or promote its activation by thrombin (18). It has been demonstrated that the platelet membrane receptor for FXI consists of the glycoprotein Ib-IX-V complex (19).…”
mentioning
confidence: 99%